2011
DOI: 10.1186/1471-2334-11-22
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis infection among homeless persons and caregivers in a high-tuberculosis-prevalence area in Japan: a cross-sectional study

Abstract: BackgroundTuberculosis (TB) is a major public health problem. The Airin district of Osaka City has a large population of homeless persons and caregivers and is estimated to be the largest TB-endemic area in the intermediate-prevalence country, Japan. However, there have been few studies of homeless persons and caregivers. The objective of this study is to detect active TB and to assess the prevalence and risk factors for latent TB infection among homeless persons and caregivers.MethodsWe conducted a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
1
22
1
1
Order By: Relevance
“…The prevalence of active TB as well as LTBI in our study was higher than that reported in New York in the US (31% of LTBI) [10] and in the Airin district in Japan (1.5% and 50.6% rate of active TB and LTBI, respectively) [9]. The higher rate of active TB and LTBI among homeless people in Seoul reflects the higher prevalence of active TB in South Korea (115 per 100 000 persons) compared with the US (4.7 per 100 000 persons) and Japan (27 per 100 000 persons) in 2009 [1].…”
Section: Discussioncontrasting
confidence: 73%
“…The prevalence of active TB as well as LTBI in our study was higher than that reported in New York in the US (31% of LTBI) [10] and in the Airin district in Japan (1.5% and 50.6% rate of active TB and LTBI, respectively) [9]. The higher rate of active TB and LTBI among homeless people in Seoul reflects the higher prevalence of active TB in South Korea (115 per 100 000 persons) compared with the US (4.7 per 100 000 persons) and Japan (27 per 100 000 persons) in 2009 [1].…”
Section: Discussioncontrasting
confidence: 73%
“…A survey performed by the Ministry of Health, Labor and Welfare, Japan in 2006 estimated that 35.4% of men and 6.9% of women were habitual drinkers (persons who drink 330 g of ethanol per day on 33 days per week). A recent study of active or latent tuberculosis in the Airin district reported that the proportion of current drinkers (persons who drink 310 g of ethanol nearly every day) was 51.9%, 25 which is similar to the proportion of habitual drinkers in our study (54.7%). The mean alcohol consumption of homeless people in the district was 40.7 1 53.5 g of ethanol per day (unpubl.…”
Section: N Japan the Spread Of Hcv Infection Has Beensupporting
confidence: 89%
“…For tuberculosis (excluding a study from Japan 48 ), estimates ranged from 0·2% to 7·7%, with substantial heterogeneity (χ 2 =123, p<0·0001; I 2 =84%, 95% CI 76–89). The random-effects pooled prevalence was 1·1% (95% CI 0·8–1·4).…”
Section: Resultsmentioning
confidence: 99%